A Study of Speech Acts in Computer Products Advertisements - Adolf Richardo Bagus Setiadi (Lexicon, 2014)
This research, which is entitled “A Study of Speech Acts of Computer Products Advertisements ”aims to find out the illocutionary acts that exist in computer products advertisements. To get the results, the data were collected through library research. The data were collected from various foreign computer magazines. The result shows that there are two patterns of illocutionary acts that exist in computer products advertisement. i.e. assertive-expressive and directive- expressive.